Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

simplify the following expression:
12a+9b2a-13a2b2+4ab2-16a


Sagot :

eu99li
[tex]12a+9b^2a-13a^2b^2+4ab^2-16a= \\ =12a-16a+9ab^2+4ab^2-13a^2b^2= \\ =-4a+13ab^2-13a^2b^2= \\ =a(-4+13b^2-13ab^2)[/tex]
12a + 9ab² - 13a²b² + 4ab² - 16a
12a - 16a + 9ab² + 4ab² - 13a²b²
-4a + 13ab² - 13a²b²